Pilot study of physiotherapist-led versus music therapist-led breathing control exercises for young adults living with breathing pattern disorder: a randomised controlled trial protocol. Issue 1 (14th September 2022) - Lewis, Adam; Kal, Elmar; Nolan, Claire Marie; Cave, Phoene; Grillo, Lizzie; Conway, Joy; Jones, Mandy
Abstract : Introduction: Breathing pattern disorder (BPD) is an abnormal breathing pattern associated with biochemical, biomechanical and psychophysiological changes. While physiotherapy is often offered, limited evidence-based therapies for BPD are available. Music therapy-based singing exercises have been shown to improve quality of life for individuals with respiratory conditions and may also be beneficial for individuals living with BPD. No study has previously compared these participatory interventions in the treatment of people living with BPD. Methods and analysis: This is a study protocol for an assessor blinded 1:1 randomised controlled trial and qualitative interview study. Forty participants aged 18–40 years who score at least 19 on the Nijmegen Questionnaire (NQ) and do not have any underlying respiratory conditions will be recruited. Participants will be randomised to receive either physiotherapy-led or music therapy-led breathing exercises for 6 weeks. The primary outcome will be between-group difference in NQ post-intervention. Semistructured interviews with a purposive sample of participants will be performed. Qualitative data will be analysed using thematic analysis to better understand participants' intervention and trial experiences. Ethics and dissemination: This study has received ethical approval by Brunel University London College of Health, Medicine and Life Science's Research Ethics Committee (32483-MHR-Mar/2022-38624-3). The anonymised completed dataset will be made available as an open-access file via Brunel University London Figshare and the manuscript containing anonymised patient data will be published in an open-access journal. Trial registration number: This trial is registered on the Open Science Framework Registry (https://osf.io/u3ncw ).